Local government reforms in Nepal - Gautam, Prem Raj
According to the author the brief outline of the local government reforms in Nepal illustrates the deliberate efforts of the government towards implementing decentralization policies. Although, the Decentralization Act provides greater autonomy to the local panchayats for decision making process in the formulation, implementation and evaluation of local level development projects, and inmobilizing local resources for these purposes, experience to date have been far from satisfactory. Thus, the capacity of the Nagar Panchayats in delivering an array of essential urban service have been extremely weak. In other words, the Town Panchayats have neither played significant role in urban development nor been able t
Keywords: Reform - Nepal; Local Government - Nepal